Imageamento magneto-ótico quantitativo em filmes finos supercondutores bicamada e com gradiente nanométrico de espessura - Pinheiro, Lincoln Brum Leite Gusmão (Universidade Federal de São Carlos, 2019)
Vortex matter in superconductors has been the focus of research of both theoretical and experimental groups around the world. When developing superconducting devices patterned on thin films one should bear in mind that flux avalanches might occur for some materials at a certain range of applied fields and temperatures. For example, technological applications of NbN thin films may be threatened by the occurrence of magnetic flux avalanches of thermomagnetic origin appearing in a large portion of the superconducting phase. This work deals, in parallel, with two distinct superconducting thin film systems by the technique of quantitative magneto-optical imaging: A bi-layered specimen composed by overlapped layers of Nb and NbN and wedge-shaped superconducting thin films of V3Si and Pb. AC susceptibility and DC magnetometry were used to characterize both the single and multiple-layer films. Magneto-optical imaging reveals interesting features of the dendritic flux avalanches in the bi-layer system, including halo-like patterns around them, and crossing avalanches. The wedge-shaped systems opened a new way to tune the critical current in the film and allowed us to study the resulting changes in the flux penetration patterns along the film. The observation of flux avalanches reported here implies that, as usual, attention to this feature must be given when films with variable thickness and bi-layers are envisaged for possible applications.
Quantitative magneto-optical imaging in bi-layered and in nanoscale wedge-shaped superconducting thin films
Keywords: Supercondutividade; Avalanches de fluxo; Bicamada supercondutora; Filmes finos em forma de cunha; Evaporação térmica; Superconductivity; Flux avalanches; Superconducting bi-layer; Wedge-shaped thin films; Thermal evaporation; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS MAGNETICOS E PROPRIEDADES MAGNETICAS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::SUPERCONDUTIVIDADE; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::SUPERFICIES E INTERFACES; PELICULAS E FILAMENTOS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA